Joint work is not shifted proximally after a long run in rearfoot strike runners - Melaro, J. A.; Gruber, A. H.; Paquette, M. R. (Journal of Sports Sciences, 2020)
Distal-to-proximal redistribution of joint work occurs following exhaustive running in recreational but not competitive runners but the influence of a submaximal run on joint work is unknown. The purpose of this study was to assess if a long submaximal run produces a distal-to-proximal redistribution of positive joint work in well-trained runners. Thirteen rearfoot striking male runners (weekly distance: 72.6 ± 21.2 km) completed five running trials while three-dimensional kinematic and ground reaction force data were collected before and after a long submaximal treadmill run (19 ± 6 km). Joint kinetics were calculated from these data and percent contributions of joint work relative to total lower limb joint work were computed. Moderate reductions in absolute negative ankle work (p = 0.045, Cohen`s d = 0.31), peak plantarflexor torque (p = 0.004, d = 0.34) and, peak negative ankle power (p = 0.005, d = 0.32) were observed following the long run. Positive ankle, knee and hip joint work were unchanged (p < 0.05) following the long run. These findings suggest no proximal shift in positive joint work in well-trained runners after a prolonged run. Runner population, running pace, distance, and relative intensity should be considered when examining changes in joint work following prolonged running.